Medical examinations of drivers for health reasons performed in compliance with the Road Traffic Act in the Podlaski Regional Centre of Occupational Medicine in Białystok in the years 2005-2009 - Piątkiewicz, Jacek Antoni; Komorowska, Ewa; Szpak, Andrzej; Gołębiewska, Ewa (Polish Journal of Public Health, 2012)
Introduction. Health examinations of drivers in Poland have been limited practically to examining candidates for drivers, to periodic testing of drivers involved in road transport and, to a lesser extent, to medical examinations under Article 122.1.3a,3b,4 of the Road Traffic Act. Since a novel Act on vehicle drivers is expected to enter into force on January 19th, 2013, this latter legal basis will undergo a significant change.Aim. The aim of the study was to provide quantitative and qualitative characteristics of drivers who had undergone medical examinations in the Podlaski Regional Centre of Occupational Medicine in Bialystok in the years 2005-2009 due to being involved in road accidents, drunk driving or referred by decision of the District Foreman due to health-related reservations.Material and methods. The data concerning drivers examined for health reasons were obtained through research conducted in the Podlaski Regional Centre of Occupational Medicine in the years 2005-2009. Among the drivers, 558 were examined after road accidents (Article 122.1.3a), 6,681 due to driving under influence of alcohol (Article 122.1.3b) and 210 were referred by decision of the District Staroste because of health status concerns (Article 122.1.4).Results. Men were predominant in all groups of drivers (around 90%). In the group of drivers involved in road accidents nearly a half (48.9%) was composed of young drivers in the age to 30 years and the older drivers aged above 55 years accounted for only 7.3%. In the group of drivers driving under influence of alcohol young drivers participated also in high proportion – 32.2%. There were 18% of negative medical certificates and also 18% of negative medical certificates in the group of drivers driving under influence of alcohol.Conclusions. High percentage of young males in the group of drivers participating in road accidents and in the group of drivers driving under influence of alcohol is the significant problem of road safety in the Podlaskie Voivodeship. It is advisable to maintain and to extend the opportunities to medically examine the drivers participating in road accidents and the drivers driving under influence of alcohol.